2021
DOI: 10.1007/s42770-021-00612-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of bufotenine against RNA and DNA viruses

Abstract: Bufotenine, an alkaloid that can be found in plant extracts and skin secretions of amphibians, is reported to have potential antiviral activity. The present study evaluated the antiviral activity of bufotenine against different genetic lineages of rabies virus (RABV, a single-stranded, negative-sense RNA virus), canine coronavirus (CCoV, a positive-sense RNA virus) and two double-stranded DNA viruses (two strains of herpes simplex virus type 1/HSV-1 [KOS and the acyclovir-resistant HSV-1 strain 29R] and canine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Due to high toxicity of the conventional antiviral drugs, numerous natural substances are being recently tested to conceive new therapeutics against viral infections. On this regard, natural products, such as bufotenine, an alkaloid obtained by skin secretions of amphibians and plant extracts, did not show potential antiviral activity against CCoV infection [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to high toxicity of the conventional antiviral drugs, numerous natural substances are being recently tested to conceive new therapeutics against viral infections. On this regard, natural products, such as bufotenine, an alkaloid obtained by skin secretions of amphibians and plant extracts, did not show potential antiviral activity against CCoV infection [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…When determining the effectiveness of the proposed interventions, five (3.65%) were shown not to be effective [ 84 , 107 , 126 , 131 , 139 ], three (2.19%) were somewhat effective [ 21 , 46 , 53 ], and 128 (93.43%) were effective as potential managements for resistant strains of HSV [ 1 - 3 , 6 - 20 , 22 - 45 , 47 - 52 , 54 - 56 , 58 - 83 , 85 - 106 , 108 - 125 , 127 - 130 , 132 - 138 ].…”
Section: Reviewmentioning
confidence: 99%
“…When determining the effectiveness of the proposed interventions, five (3.65%) were shown not to be effective [84,107,126,131,139], three (2.19%) were somewhat effective [21,46,53], and 128 (93.43%) were effective as potential managements for resistant strains of HSV [1][2][3][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][47][48][49][50][51][52][54][55][56][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]…”
Section: Data Extractionmentioning
confidence: 99%
“…Norpsilocin, baeocystin, norbaeocystin, aeruginascin, and bufotenin ( 67 – 71 , Figure 5 ) are other examples of indoles with psychoactive properties produced by mushrooms, although they have not been studied much other than psilocin or psilocybin [ 21 , 108 ]. The syntheses and biological evaluation of some of these were carried out by Sherwood et al (2020) [ 108 ], and the antiviral activity of bufotenine ( 71 ) was reported [ 109 ]. Norpsilocin ( 67 ) was isolated for the first time in 2017 (from Psilocybe cubensis ) and its psychoactive properties, with an agonist activity of the human 5-HT 2A receptor close to that of psilocin ( 64 ), were also described [ 110 ].…”
Section: New Alkaloids Found In Mushroom Since 2002mentioning
confidence: 99%